2019
DOI: 10.2172/1580213
|View full text |Cite
|
Sign up to set email alerts
|

Grid-Interactve Efficient Buildings Technical Report Series: Lighting and Electronics

Abstract: These definitions are for the purposes of the Grid-interactive Efficient Buildings Technical Report Series. They may be defined differently or more generally in other contexts. Grid services Services that support the generation, transmission, and distribution of electricity and provide value through avoided electricity system costs (generation and/or delivery costs); this report focuses on grid services that can be provided by grid-interactive efficient buildings. Distributed energy resource (DER) A resource s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
2
0
1
Order By: Relevance
“…Los sistemas de automatización de edificios pueden importar el precio de la electricidad de la red y el factor de intensidad de carbono en tiempo real y comunicar el potencial de reducción de la demanda a la red a través del sensor bidireccional y el protocolo de comunicación. Adaptado de Nubbe y Yamada 2019 230 © 2019 Guidehouse Inc.…”
Section: Edificios Eficientes De Red Eléctrica Interactivaunclassified
“…Los sistemas de automatización de edificios pueden importar el precio de la electricidad de la red y el factor de intensidad de carbono en tiempo real y comunicar el potencial de reducción de la demanda a la red a través del sensor bidireccional y el protocolo de comunicación. Adaptado de Nubbe y Yamada 2019 230 © 2019 Guidehouse Inc.…”
Section: Edificios Eficientes De Red Eléctrica Interactivaunclassified
“…Lighting and equipment are major energy consumers, especially in commercial buildings. Their energy efficiency aspects focus on improving the efficiency of the systems and developing control strategies that can reduce the time of usage [46,51,52]. For instance, numerous studies revealed that the use of light emitting diode (LED) lamps can significantly reduce energy use compared to other lighting types.…”
Section: Building Energy Efficiencymentioning
confidence: 99%
“…The most well-established and mature DSM resources are energy efficiency and demand response. Table 1 lists technologies suitable for GEB applications [25,35,51]. Examples of market-available dynamic envelope technologies that have high potential for GEB applications are dynamic windows, automated attachments, and thermal storage.…”
Section: Grid-interactive Efficient Buildingsmentioning
confidence: 99%